Country Crisis: A Content Analysis of Rural Opioid Epidemic News Coverage - Cara R. Lawson; Courtney Meyers (Journal of Applied Communications, 2020)
The spread of non-prescription opioid abuse has increased to the point that a person is now more likely to die from an accidental overdose than an automobile accident. Rural areas have been hit particularly hard, and many farmers indicate direct impacts resulting from the opioid epidemic. Researchers have recognized the role of the media in communicating complicated issues and influencing potential solutions. This study analyzed the frames and sources used to communicate issues regarding the rural opioid epidemic in The New York Times and five additional newspapers from states most affected by the opioid epidemic. A total of 115 news, feature, editorial, and other articles were analyzed. The most often used frame was “growth or spread” of the epidemic and the sources most frequently referenced were medical professionals and elected officials. Although a non-traditional issue in agriculture, agricultural communicators should not shy away from getting involved given the potential for harm to rural communities and, in turn, the agriculture industry. Future studies should investigate rural community member and journalist perceptions on the issue, as well as coverage in other states.
Keywords: framing; content analysis; rural opioid